2022
DOI: 10.1108/ajim-08-2021-0232
|View full text |Cite
|
Sign up to set email alerts
|

Fake or real news? Understanding the gratifications and personality traits of individuals sharing fake news on social media platforms

Abstract: Purpose“Fake news” or misinformation sharing using social media sites into public discourse or politics has increased dramatically, over the last few years, especially in the current COVID-19 pandemic causing concern. However, this phenomenon is inadequately researched. This study examines fake news sharing with the lens of stimulus-organism-response (SOR) theory, uses and gratification theory (UGT) and big five personality traits (BFPT) theory to understand the motivations for sharing fake news and the person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 186 publications
(345 reference statements)
0
20
0
Order By: Relevance
“…Second, SOR theory is ideal for examining its components' unidirectional cause and effect association (Sampat and Raj, 2022). The present study intends to investigate the unidirectional cause and effect association of health consciousness, facilitators and barriers to the preference for the hybrid working model.…”
Section: Stimulus-organism-response Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Second, SOR theory is ideal for examining its components' unidirectional cause and effect association (Sampat and Raj, 2022). The present study intends to investigate the unidirectional cause and effect association of health consciousness, facilitators and barriers to the preference for the hybrid working model.…”
Section: Stimulus-organism-response Theorymentioning
confidence: 99%
“…Customer behaviour results from various influences that can potentially boost and diminish intentions. Past scholars have termed these influences as facilitators (that enhance the intentions) and barriers (inhibit the intentions) (Sampat and Raj, 2022). Shao et al (2021) suggested that specific facilitators and inhibitors govern the employees' decision to choose the next day's working location.…”
Section: Barriers To the Hybrid Work Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…People share information to escape from reality, pass time, and for entertainment purposes as their habit (Taghipanahi et al, 2020). It was found that information sharing along with pass time and socialization motivates people to share news instantly on social media (Sampat & Raj, 2022). There has been a significant influence of information sharing gratification on news sharing on social media (Thompson et al, 2019).…”
Section: Gratification Constructs and Their Relationship With Fake Ne...mentioning
confidence: 99%
“…The use of social media during times of COVID-19 has increased globally (Putra et al, 2022). It has been suggested that pass-time gratifications lead to instant sharing of news on social media platforms (Ghaznavi et al, 2022;Sampat & Raj, 2022). Therefore, it can be predicted that pass-time gratification and fake news sharing on COVID-19 share a positive relationship.…”
Section: Pass Timementioning
confidence: 99%